Viremia in acute herpes zoster (2009)
A phase 2 trial was conducted to evaluate the efficacy of a topical antiviral, sorivudine, as an adjuvant to valacyclovir for the treatment of acute herpes zoster. In this randomized, placebo-controlled, double-blind trial, 25 patients were treated with either sorivudine or placebo cream. All patients began 7 days of valacyclovir treatment on day 3. Zoster lesion swab samples and samples of peripheral blood mononuclear cells were collected periodically throughout the study and were analyzed for varicella-zoster virus (VZV) DNA by use of both qualitative and real-time polymerase chain reaction. Serum samples collected periodically throughout the study were analyzed for VZV DNA by use of real-time polymerase chain reaction. VZV DNA was detected in all 3 sample types, and the number of viral copies correlated with the progression of herpes zoster. No statistically significant differences were seen between the placebo- and sorivudine-treated groups with respect to clinical characteristics or laboratory test results. The detection of VZV DNA in the serum and peripheral blood mononuclear cells of all 25 zoster patients documents that viremia is a common manifestation of herpes zoster. Sorivudine cream appears to be a safe and well-tolerated adjuvant therapy; however, further phase 2 studies are needed to determine its clinical efficacy for the treatment of herpes zoster. Trials registration. ClinicalTrials.gov identifier: NCT00652184.